The Impact of Management Accounting Systems, Eco-Innovations and Energy Efficacy on Firm’s Environmental and Economic Performance - Zandi, Gholam Reza; Ghani, Erlane K.; Lestari, Retno Martanti Endah; Maimunah, Siti (International Journal of Energy Economics and Policy, 2019)
The current study aims to explore the effect of ecological innovations, energy efficiency and management accounting systems in influencing firms’ environmental performance of Indonesian manufacturing companies. The study further analyzed the relationship of ecological innovation, energy efficiency, and management accounting system with an organization’s economic performance. The present study is therefore novel in addressing the vital connection of technology with organizations’ performance in ecologically driven settings. The total valid sample for the present study is 310. The results of PLS-SEM confirm that all selected variables have a positive and significant impact on economic performance and environmental performance in the manufacturing sector in Indonesia. Moreover, the outcomes of the PLS-SEM confirm that economic and environmental performances have positively and expressively impacted by management accounting system, energy efficiency, and ecological innovations. The outcomes of partial least square structural equation modeling also indicate that efficient and better utilization of energy and management accounting system provide an improve economic and environmental condition for the Indonesian manufacturing sector. The study further recommended that the government needs to regulate some policy in which adoption of the management accounting system for all small, medium and large firms are compulsory in order to get sustainable development and environment. Keywords: Management accounting system, energy efficiency, environmental performance, Indonesia. JEL Classifications: Q55, Q43 DOI: https://doi.org/10.32479/ijeep.8364